A Socio-Economic Conditions of Society Affected by The Development of Overpass and Double-Track Railway in The Village of Gambarsari, Kebasen District, Banyumas District - Dijan Rahajuni (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
The construction of road infrastructure in an area can displace residents who have previously inhabited the area. Likewise, the construction of double tracks and overpasses in Gambarsari Village, Kebasen District, Banyumas Regency. However, with the eviction, the Government takes action. The Government provided compensation that did not harm the community. This study aims to analyze the socio-economic conditions of the respondents who were evicted from the perspective of land area, living conditions and housing facilities, with 28 households evicted. The analysis method used a paired two-sample test by first testing the conditions for the normality of the data. The study results were that the average land area had decreased. However, as much as 57.14 percent of the respondents had an increase in land area. Respondent’s living conditions are all getting better with permanent buildings and there is also an increase in the score of living conditions for 67.86 percent of respondents. The condition of facilities where the respondents lived was increase in 25 percent of the respondents. The condition of the facilities includes from the good category to the complete category.